CEO Narcissism, Risk-Taking, and Resilience: An Empirical Analysis in U.S. Commercial Banks. (April 2019) - Buyl, Tine; Boone, Christophe; Wade, James B.
In this study, we investigate how CEO narcissism, in combination with corporate governance practices, impacts organizational risk-taking and how this in turn affects organizations' resilience to environmental conditions. We examine these issues in the context of the recent collapse (systemic shock) of the U.S. banking industry in September 2008, using a sample of 92 CEOs from 2006 until 2014. We find that before the shock CEO narcissism positively affected the riskiness of banks' policies, especially when compensation policies that encourage risk-taking (stock options) are in place. The positive effect of narcissism was dampened, however, when board monitoring was more effective (because of the presence of knowledgeable outsider directors). Furthermore, we find that these preshock features hamper organizations' resilience to (economic) shocks, as banks led by more narcissistic CEOs before the September 2008 collapse experienced a slower recovery to preshock performance levels afterwards. This effect was partially mediated by banks' preshock riskiness of policies. We attribute these effects to the associated depletion of the organizations' internal resources (beyond slack). Post-hoc analyses further underscore this idea, showing that the U.S. government's capital injections through the Troubled Assets Relief Program (TARP)—resolving the "problem" of resource depletion—moderated these effects.